Effectiveness of two disinfectant solutions and microwave irradiation in disinfecting complete dentures contaminated with methicillin-resistant Staphylococcus aureus - Altieri, Karen Tereza [UNESP]; Sanitá, Paula Volpato [UNESP]; Machado, Ana Lucia [UNESP]; Giampaolo, Eunice Teresinha [UNESP]; Pavarina, Ana Cláudia [UNESP]; Vergani, Carlos Eduardo [UNESP] (Elsevier, 2012)
Methicillin-resistant Staphylococcus aureus (MRSA) biofilm on dentures can be aspirated, thus causing infections such as aspiration pneumonia. The authors evaluated the efficacy of two disinfectant solutions and microwave irradiation in disinfecting complete dentures contaminated with MRSA. Methods. The authors contaminated 36 simulated complete dentures with MRSA and divided them into four equal groups: a positive control group consisting of dentures that were not disinfected; a group that soaked in 1 percent sodium hypochlorite for 10 minutes; a group that soaked in 2 percent chlorhexidine gluconate for 10 minutes; and a group that underwent microwave irradiation at 650 watts for three minutes. The authors quantified colony counts and evaluated the long-term effectiveness of disinfection. Results. All dentures from the control group showed substantial microbial growth on the plates (6.24 log10 colony-forming units per milliliter). The authors observed no evidence of microbial growth on plates of any disinfected dentures. After seven days' incubation, the authors observed broth turbidity in all beakers containing the dentures disinfected with 1 percent sodium hypochlorite. Conclusions. Soaking in chlorhexidine gluconate solution and microwave irradiation resulted in complete disinfection of all dentures contaminated with MRSA in both the short and the long term. Soaking in sodium hypochlorite solution was effective only as a short-term disinfectant. Clinical Implications. Microwave irradiation and 2 percent chlorhexidine gluconate may have a disinfective application in dental offices and institutions in which denture wearers are treated, thus improving the longevity and quality of life of patients and reducing the burden of disease caused by MRSA.
Keywords: Complete dentures; Disinfectants; Disinfection; Methicillin-resistant Staphylococcus aureus (MRSA); Microwave irradiation